Young Entrepreneurs Perspectives on Success in Managing a Startup Business - Anggy Giri Prawiyogi; Aang Solahudin (Pandawan Sejahtera Indonesia, 2023)
A person's viewpoint on something related to a purposeful life orientation is what is meant by their perception of success. Each person has their own subjective definition of success. The definition of success varies among young business people because they have diverse standards for what constitutes a successful enterprise. This study aims to determine how business owners evaluate the achievement of their ventures. Two Acehnese company owners with new ventures comprised the study's respondents. Detailed interviews with each respondent were done to collect research data. The theory of Perception of Success served as the foundation for the interview questions. The results of the interviews demonstrate that success is perceived differently depending on what success means to each person. According to Respondent I, a successful business